e-Proceedings of the 5th International Conference on Linguistics, Literature and Culture (ICLLIC) 2019: Change and Preservation in Language and Culture in Asia - Asl, Moussa Pourya (School of Humanities, Universiti Sains Malaysia, 2019)
The present e-proceedings “Change and Preservation in Language and Culture in Asia” has been made possible thanks to the commitment of individuals who contributed much time and energy in assisting with a number of technical matters from the beginning until the final stages of the publication process. We would also like to express our appreciation for the contribution of the English Language Studies section and administrative staff of the School of Humanities for assisting with various matters. Finally, thanks must be given to the authors of the extended abstracts in this publication for their willingness to share the findings of their work in progress with other academics and researchers in the areas of language, linguistics and culture